A new target for proteasome inhibitors: FOXM1 - Gartel, Andrei L. (2010)
IMPORTANCE OF THE FIELD: The proteasome is responsible for ubiquitin- and ATP-dependent proteolysis of cellular proteins. The latest advances in proteasome studies led to the development of proteasome inhibitors as drugs against human cancer. It has been shown that proteasome inhibitors selectively kill cancer, but not normal cells. However, the exact mechanisms of the anticancer activity of proteasome inhibitors are not well understood. The oncogenic transcription factor Forkhead Box M1 (FOXM1) is overexpressed in a majority of human carcinomas, while its expression is usually low in normal cells. In addition, FOXM1 may also drive tumor invasion, angiogenesis, and metastasis. For these reasons, FOXM1 is an attractive target for anticancer drugs. AREAS COVERED IN THIS REVIEW: My aim is to discuss the recent publications that may point out to novel mechanism of action of proteasome inhibitors. In addition, I will describe the identification of new types of proteasome inhibitors, called thiazole antibiotics. Using a cell–based screening system the thiazole antibiotics Siomycin A and thiostrepton were isolated as inhibitors of FOXM1 transcriptional activity and expression. Paradoxically, it has been showed that these drugs also stabilize the expression of other proteins and act as proteasome inhibitors in vitro. Moreover, it was found that well-known proteasome inhibitors, such as MG115, MG132 and bortezomib inhibit FOXM1 transcriptional activity and FOXM1 expression. WHAT THE READER WILL GAIN: It has been shown that proteasome inhibitors suppress FOXM1 expression and simultaneously induce apoptosis in human tumor cell lines. This review describes the correlation between negative regulation of FOXM1 by proteasome inhibitors and apoptosis, and suggests that negative regulation of FOXM1 is a universal feature of these drugs and it may contribute to their anticancer activity. TAKE HOME MESSAGE: Oncogenic transcription factor FOXM1 is upregulated in a majority of human cancers, suggesting that growth of cancer cells may depend on FOXM1 activity. A short time ago, it has been shown that proteasome inhibitors simultaneously inhibit FOXM1 expression and induce apoptosis in human cancer cells. This effect may explain specificity of proteasome inhibitors to induce apoptosis in cancer, but not in normal cells. Now it is critical to determine the role of suppression of FOXM1 in apoptosis induced by proteasome inhibitors and to establish how significant is the inhibition of FOXM1 for the anticancer activity of proteasome inhibitors.